The development of practical guidelines for designing online questionnaires - Saaya, Zurina; Mustafa, Nuridawati; Devaraju, Anusuriya (2007)
Questionnaires are an inexpensive way to gather data from a potentially large number of respondents. However, it is a long and effort consuming process to conduct the survey manually. As the popularity of the Internet increases, online survey creation software allows an access to individuals in distant locations, the ability to reach difficult to contact participants, and the convenience of having automated data collection, which reduces researcher time and effort. The aim of this study is to develop an Online Questionnaire Builder (OQB), which is an online survey software package to streamline and simplify the entire survey process from design of the questionnaire to the presentation of the results. OQB consists of an intuitive wizard interface for creating surveys, tools for distributing the surveys and analyzing the results. This paper presents the results of our preliminary study. By studying wide numbers of existing surveys, we came up with practical guidelines that should be met before a questionnaire can be considered a sound research tool. The guidelines presented in terms of structure, layout, navigation, formatting, response format and question types. It is expected, with the specified guidelines, OQB will be a useful and automated online application for creating and distributing surveys for the use of researchers or any scholars.